Penerapan Model Kooperatif Tipe Jigsaw dalam Pembelajaran IPS dI SD - Meti Nur Fajri Sari; Aren Frima; Candres Abadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the completeness of the learning outcomes of fifth grade students of Negeri Al Ilmu Lubuklinggau after using the Jigsaw Type Cooperative learning model. The method used is a quantitative research method with a quasi-experimental research design in the one group pre-test and post-test group category. The sampling technique used is saturated sampling technique. Data collection techniques using multiple choice tests. Data analysis techniques consist of prerequisite analysis techniques and hypothesis testing. The analysis prerequisite testing technique uses the normality test while the hypothesis used is the one-sample z-test. The results showed that the pre-test average was 46,15 with a completeness percentage of 0% or no students passed while the post-test average was 84,15 with a completeness percentage of 88.40% or 23 students who passed. The results of the z-test analysis obtained zcount (6.64) ≥ ztable (1.64). The conclusion is that the application of the Jigsaw Cooperative Type model to the social studies learning outcomes of fifth grade students is significant.. Keywords: Application, Jigsaw Type Cooperative Model, Social Studies Learning Outcomes